1999
DOI: 10.1097/00005537-199908000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin Does Not Inhibit the Tumoricidal Efficacy of Cisplatinum

Abstract: This study is the first demonstration that fosfomycin does not inhibit the tumoricidal efficacy of cisplatinum in vivo. This suggests that fosfomycin may be useful in preventing cisplatinum-induced ototoxicity and nephrotoxicity in humans without altering the tumor response rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…Until recently most studies about cisplatin ototoxicity evaluated cochlea functional alterations through action potential, somation potential and cochlear microphonics or through Brainstem Evoked Auditory Potentials (BAEP 11,[14][15][16][17][18][19] . Several of these drugs have in vivo collateral effects and little is known about a possible interference action on the anti-neoplastic activity of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently most studies about cisplatin ototoxicity evaluated cochlea functional alterations through action potential, somation potential and cochlear microphonics or through Brainstem Evoked Auditory Potentials (BAEP 11,[14][15][16][17][18][19] . Several of these drugs have in vivo collateral effects and little is known about a possible interference action on the anti-neoplastic activity of cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that levels of glutathione (GSH) and antioxidant enzymes as superoxide dismutase (SOD), catalase, GSH peroxidase and GSH reductase are reduced in these tissues leading to lipid peroxidation, thus, to cellular toxicity. 3,12,15,17,18 Anti-oxidant effects of Hyperbaric Oxygen Therapy have been observed through decrease in neutrophils adhesion 22 and increased NO production, which combine with superoxide anions blocking their effects. 23 In experimental pancreatitis in rats, it was demonstrated that HOT promotes an elevation in levels of super oxide dismutase (SOD) with metabolization of oxidant radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assim, propõem que a otoproteção deve atuar nos mecanismos de anti-oxidação, podendo-se atuar em três pontos básicos: 1) prevenção da formação de oxigênio reativo, 2) neutralização de produtos tóxicos da peroxidação lipídica e 3) bloqueio às substâncias que causam dano à membrana das células sensoriais, bloqueando os mediadores de apoptose. 33,34 Diferentes substâncias vêm sendo testadas no intuito de otoproteção a cisplatina, como: dietilcarbamato, ácido 4-metiltiobenzóico, ebselen, melatonina, ácido lipóico 9,40,42,43,45 , acetil cisteína 38 , fosfomicina 47 , neurotrofinas 39 , análogos do ACTH. 20,41,44 Muitas destas substâncias têm efeitos colaterais in vivo e não se sabe sobre sua possível atuação bloqueando os efeitos antineoplásicos da cisplatina.…”
Section: Discussionunclassified
“…10,[27][28][29][30][31][32][33][34] Diversas drogas têm sido testadas com o objetivo de otoproteção como o tiossulfato de sódio, o dietilcarbamato, o ACTH e derivados, o ácido 4-metilthiobenzóico, o ácido lipóico, o glutation e seus ésteres, metionina, procaína, hormônio estimulador alfa-melanocítico (melatonina), antioxidantes como a ginkgo biloba e fosfomicina e compostos sulfurados. 3,5,6,9,[35][36][37][38][39][40][41][42][43][44][45][46][47] Trabalho recente de tese de mestrado da FMRP -USP mostrou que baixas doses de gentamicina levam a um efeito protetor estrutural para as células ciliadas externas, que mantém suas características normais à microscopia eletrônica de varredura quando se aplicam, posteriormente, doses elevadas desta droga, sugerindo assim, que existe um mecanismo de autodefesa -adaptação intra-coclear às agressões induzidas pelas drogas ototóxicas. [48][49][50][51] O objetivo da investigação é verificar se existe o efeito otoprotetor de drogas que já são utilizadas na prática clínica com outras finalidades como o extrato de ginkgo biloba, aos danos cocleares causados pela cisplatina, utilizando doses de cisplatina sabidamente ototóxicas, lesivas às células ciliadas externas, avaliando-se as alterações anatômicas através da microscopia eletrônica de superfície, e avaliação funcional por emissões otoacústicas -produtos de distorção.…”
Section: Introductionunclassified